2012
DOI: 10.3920/jcns2012.x208
|View full text |Cite
|
Sign up to set email alerts
|

Network centrality and multiplexity: a study of sales performance

Abstract: Network literature suggests that individual embeddedness leads to performance. The authors argue that resources from intra-firm social networks are critical for gaining advantages. The contribution of the paper lies at the performance impact of the network position. Previous studies have considered two alternative views, degree and closeness, of network centrality that have been shown to impact job promotion, innovation diffusion, and wage increase. To our knowledge no work has been done to identify the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Multiplexity has been shown to positively influence individuals' work-related outcomes, such as job performance (e.g., Cai et al, 2018;Claro et al, 2012), career achievement (Cotton et al, 2011), and entrepreneurial success (Newbert et al, 2013;Newbert & Tornikoski, 2012). To illustrate, Claro et al (2012) found that multiplexity of intrafirm social relations between salespeople improves job performance by motivating knowledge sharing between salespeople and opening up enhanced sales and margin opportunities. However, multiplexity may not always be beneficial.…”
Section: Current State Of Multiplexity Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiplexity has been shown to positively influence individuals' work-related outcomes, such as job performance (e.g., Cai et al, 2018;Claro et al, 2012), career achievement (Cotton et al, 2011), and entrepreneurial success (Newbert et al, 2013;Newbert & Tornikoski, 2012). To illustrate, Claro et al (2012) found that multiplexity of intrafirm social relations between salespeople improves job performance by motivating knowledge sharing between salespeople and opening up enhanced sales and margin opportunities. However, multiplexity may not always be beneficial.…”
Section: Current State Of Multiplexity Researchmentioning
confidence: 99%
“…Unlike the intersectionality and faultlines literatures, the multiplexity literature has solely relied upon quantitative measures. Multiplexity is typically assessed via self-reported information on the number of different social relations within dyads contained in an individual’s social network (e.g., Claro et al, 2012; Ibarra, 1992; C. M. Smith & Papachristos, 2016).…”
Section: An Overview Of Multidimensionalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a study with MBA students showed that different types of support (i.e., career & psychosocial support) were associated with higher career satisfaction (Murphy and Kram 2010). Moreover, multiplex support has also been associated with actual increased work performance, possibly because it has enabled individuals to systematically address knowledge which in turn has helped them to perform (Claro et al 2012). We transfer this reasoning with regards to peer support networks in higher education and aim to examine:…”
Section: Multiplex Peer Supportmentioning
confidence: 99%